Technology in the classroom EFL teachers' technological pedagogical and content knowledge = Tehnologija u razredu : tehnološka pedagoška i sadržajna znanja učitelja EFL-a - Mukminin, Amirul; Habibi, Akhmad; Fridiyanto (2020)
This is a mix-method study with a sequential explanatory design aimed at investigating the level of technology knowledge of EFL teachers in Indonesian senior high schools. In this study, a total number of 375 teachers from public schools located in the southern part of Sumatra Island, Indonesia, were voluntarily involved in the survey. To fit the context of the study, the TPACK survey was adapted from previous literature with the overall Cronbach’s alpha ranging from .82 to .89. The adapted instruments were validated through content validity involving four experts in educational technology and one expert of English-Indonesian language translation. We also applied Cronbach’s alpha testing, the reliability of the adapted instruments (0.75 to .89). Mean and p-value were reported in the quantitative report. Afterward, we interviewed teachers using semi-structured interview which questions were based on the survey items. The data were transcribed, translated, coded, and put into themes. Findings showed that all teachers had more knowledgeable of traditional, non-technological conception of pedagogy, and content than technological pedagogy and technological content.
Ovo je studija kombinirane metode s uzastopnim obrazloženjem usmjerenom na ispitivanje razine tehnološkog znanja nastavnika EFL-a u srednjim školama u Indoneziji. U ovom istraživanju dobrovoljno je uključeno ukupno 375 učitelja iz javnih škola smještenih u južnom dijelu otoka Sumatre u Indoneziji. Kako bi se prilagodio kontekstu studije, TPACK istraživanje je prilagođeno iz prethodne literature s ukupnim Cronbachovim alfa rasponom od .82 do .89. Prilagođeni instrumenti su potvrđeni valjanošću sadržaja koja uključuje četiri stručnjaka za obrazovnu tehnologiju i jednog stručnjaka za prijevod s engleskog na indonezijski jezik. Primijenili smo i Cronbachovo alfa testiranje, pouzdanost prilagođenih instrumenata (0.75 do 1.89). Srednja i p vrijednost su navedeni u kvantitativnom izvješću. Poslije smo intervjuirali nastavnike pomoću polustrukturiranog intervjua u kojem su se pitanja temeljila na anketnim stavkama. Podaci su prepisani, prevedeni, kodirani i stavljeni u teme. Nalazi su pokazali da su svi učitelji više poznavali tradicionalnu, netehnološku koncepciju pedagogije i sadržaje od tehnološke pedagogije i tehnološkog sadržaja.
Bibliografske bilješke na kraju teksta.
Abstract ; Sažetak.
Keywords: Školstvo -- Nastavnici -- Nastavnici engleskog jezika -- Znanje o tehnologiji; Indonezija